2021
DOI: 10.1002/uar2.20008
|View full text |Cite
|
Sign up to set email alerts
|

Food safety considerations of urban agroforestry systems grown in contaminated environments

Abstract: The interest in and establishment of urban gardens and food forests has been growing in recent years. Food production in urban environments has its challenges, however, particularly regarding the safety of edible crops grown in environments that contain potential contaminants. While some studies exist on urban agriculture food safety for annual crops, the literature is limited on relative risks in urban food forests that include fruit-and nut-producing trees and shrubs. This review provides an overview of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Pulighe and Lupia [37] noted that COVID-19 exposed the weaknesses of food systems in large cities, which should be counteracted with developments in urban agriculture and the inclusion of edible green infrastructures into cities. Romanova and Lovell [38] recognized the contributions of urban gardens towards stormwater mitigation and food security, while at the same time warned about potential food health and safety risks of urban landscapes used for edibles. Hume et al [39] calculated the potentials of urban gardening in Adelaide, Australia, and concluded that self-sufficiency through backyard vegetable production is plausible.…”
Section: Investigation Background: Food Security and Home Gardening D...mentioning
confidence: 99%
“…Pulighe and Lupia [37] noted that COVID-19 exposed the weaknesses of food systems in large cities, which should be counteracted with developments in urban agriculture and the inclusion of edible green infrastructures into cities. Romanova and Lovell [38] recognized the contributions of urban gardens towards stormwater mitigation and food security, while at the same time warned about potential food health and safety risks of urban landscapes used for edibles. Hume et al [39] calculated the potentials of urban gardening in Adelaide, Australia, and concluded that self-sufficiency through backyard vegetable production is plausible.…”
Section: Investigation Background: Food Security and Home Gardening D...mentioning
confidence: 99%
“…Pollution could be one of the major problems for the safety of UPA production. However, there are several techniques and tricks to reduce it and make healthy food, which must be chosen on a case-by-case basis after a pollution assessment [64]. Notwithstanding these limitations, we believe that the methodology and the study developed can be easily transferred to other contexts for analyzing other cities and their UPA sustainability, to suggest food policy orientations, and to integrate food considerations in urban planning.…”
Section: Discussionmentioning
confidence: 99%
“…Both the phytoavailablility and bioaccumulation in food products are dependent on several different factors including soil pH, redox potential, soil clay content and soil cation exchange capacity, organic matter, aging of added elements, nature and quantity of elements, and details of the soil–plant interface such as the impact of the rhizosphere microflora and levels of root exudates (Antoniadis et al., 2017). Several papers and reviews have focused on the issue of bioaccumulation of metals in vegetables and other products (Abdullahi et al., 2021; Romanova & Lovell, 2021). Some show little plant uptake and bioaccumulation in several vegetable and agroforestry tree species.…”
Section: Urban Livestock Keeping In the United Statesmentioning
confidence: 99%